PERUBAHAN PEMERINTAHAN MUKIM DI LANGSA, 1906-1975 - Muhammad Zakir; Suprayitno Suprayitno; Warjio Warjio (Sejarah dan Budaya : Jurnal Sejarah, Budaya, dan Pengajarannya, 2019)
This article discusses the changes that took place in the mukim institutions in the structure of regional government in Langsa in the period 1906-1975. This article answers the issue of how the structure and function of the mukim institutions changed in Langsa in the period 1906-1975 and how the mukim institutions in the New Order government experienced a setback. This research uses historical methods trough four steps: heuristic (collecting historical sources); verification (critical sources review); interpretation (historical analysis and interpretation); and historiography (historical writing). Sources as the historical data which collected from several document and literature from colonial to postcolonial period. This study uses social sciences approaches especially politic, so that theme of this study is political and governmental history. This study found that the mukim institution was an original government institution that had long stood autonomously in Aceh. Mukim experienced many changes both in structure and function in the Dutch colonial era, Japanese Occupation, and the period of Revolution of Independence, and even disappeared during the New Order era. The formation of the mukim area is closely related to the existence of the regulation of social life (adat) and for religious life (law) and as well as later appearing to be a unit of local government.Artikel ini membahas perubahan yang terjadi pada lembaga mukim dalam struktur pemerintahan daerah di Langsa pada periode 1906-1975. Artikel ini menjawab permasalahan bagaimana perubahan struktur dan fungsi lembaga mukim di Langsa pada periode 1906-1975 dan bagaimana lembaga mukim dalam tatanan pemerintahan Orde Baru mengalami kemunduran. Penelitian ini menggunakan metode sejarah melalui empat tahap: heuristik (pengumpulan sumber sejarah); verifikasi (kritik sumber); interpretasi (analisis sejarah dan penafsiran); dan historiografi (penulisan sejarah). Sumber sebagai data sejarah yang diperoleh dari sejumlah dokumen dan literatur periode dari periode kolonial hingga pascakolonial. Penelitian ini menggunakan pendekatan ilmu sosial khususnya politik, sehingga tema penelitian ini adalah sejarah politik dan pemerintahan. Penelitian ini menemukan bahwa lembaga mukim merupakan lembaga pemerintah asli yang telah lama berdiri secara otonom di Aceh. Mukim mengalami banyak perubahan baik secara struktur maupun fungsi pada zaman kolonial Belanda, zaman Pendudukan Jepang, dan periode Revolusi Kemerdekaan, bahkan hilang pada era Orde Baru. Pembentukan wilayah mukim terkait erat dengan keberadaan untuk pengaturan kehidupan sosial (adat) maupun untuk kehidupan beragama (hukum) dan serta kemudian muncul menjadi unit pemerintah lokal.